HUBUNGAN BELIEF IN AFTERLIFE DENGAN KECEMASAN TERHADAP KEMATIAN (Studi pada Individu Muslim Usia 18-21 Tahun) - Zariayufa, Kayisa; Ninin, Retno Hanggarani; Widiastuti, Tiara Ratih (Psikoislamedia: Jurnal Psikologi, 2019)
The purpose of this study was to determine the relationship between belief in afterlife and death anxiety. The subjects of this study were 481 muslims ranging in age from 18 to 21 who came from various cities in Indonesia such as Bandung, Jakarta, Pekanbaru and others. Belief in afterlife was measured using Afterlife Belief Scale for Muslims consisting of three dimensions, positive afterlife belief (7 items); negative afterlife belief (5 items) and extinction (11 items) and death Anxiety Scale-Extended (52 items) was used to measure the death anxiety level. The results of this study indicated no negative relationship between positive afterlife belief and death anxiety. The results of this study also also found a positive relationship between negative afterlife belief and death anxiety but the relationship was classified as a weak relationship (r = 0.115). For the third dimension, the results of also indicated a positive relationship between extinction and death anxiety (r = 0.081). Due to the correlation coefficient, the relationshipwas also classified as weak relationship.